Software Transactional Memory: Why is it only a Research Toy? - CA&#x...CAVAL, CĂLIN; BLUNDELL, COLIN; MICHAEL, MAGED; CAIN, HAROLD W.; PENG WU; CHIRAS, STEFANIE; CHATTERJEE, SIDDHARTHA (Communications of the ACM, 2008)
The article discusses software transactional memory (STM), examining aspects of STM that undermine its initial promise including its overheads and workload applicabilities. Transaction memory (TM) is a concurrency control paradigm that provides atomic and isolated execution for regions of code, the authors states. Other topics include the performance of highly optimized STM, the poor performance of TM at low levels of parallelism, and tradeoffs which impact the performance and programmability of TM systems.